Spremembe v strokovnem šolanju in nove razsežnosti v poklicni odgovornosti medicinskih sester: (s kongresa Mednarodne zveze med. sester v Tokiu od 29. maja do 4. junija 1977) - Gradišek, Anica (Obzornik zdravstvene nege, 1977)
In the first part of the article the author speaks about the new trends in nursing education which were discussed at the 16th Congress of ICN in Tokio 1977. In the second part of the report she discusses the new dimensions of professional responsibilities which have to deal with authority, personal and collective rights and duties of nurses. The latter are obtained through good nursing as well as the work in the professional organisation which has to protect the individual and common interests of nurses.